Youth and Caregivers’ Perspective on Teens Engaged as Mentors (TEAM): An Inclusive Peer Mentoring Program for Autistic Adolescents - O’Hagan, Belinda; Sonikar, Pooja; Grace, River; Castillo, Dasha; Chen, Emily; Agrawal, Malhaar; Dufresne, Simone; Rossetti, Zach; Bartolotti, Lauren; Krauss, Shari (Journal of autism and developmental disorders, 2023)
Past studies indicate that many autistic youth benefit from support with developing social relationships, exploring leadership opportunities, and engaging in post-secondary education. Teens Engaged as Mentors (TEAM) is an innovative mentoring program that provides socialization and community engagement opportunities in a safe environment for youth with and without autism. This qualitative study explored how participants and their caregivers perceived participation in TEAM. Stakeholder focus groups were conducted annually from 2016 to 2020 with 16 autistic mentees (ages 9–13), 30 autistic and neurotypical mentors (ages 14–21), and 30 caregivers. Participants reported enjoying TEAM because of increased socialization opportunities, which promoted friendships and openness toward others. Caregivers reported growth in their children’s social skills and confidence throughout their participation.